Development of Mandarin Education Quiz Game Using Android-Based Multimedia Development Life Cycle - Topani, Muhammad Alfikri Maida; Azhari, Ahmad (Mobile and Forensics, 2023)
Mandarin is a language that is widely spoken and studied by people all over the world. Parents who start enrolling their children in Mandarin language courses from an early age with the hope that their children will become accustomed and proficient in using Mandarin. However, for elementary school children, the difficulty of constructing sentences in Mandarin is a major obstacle for children in the process of learning Mandarin. The purpose of this research is to create a unity-based mandarin quiz educational game application that is useful as an alternative media in the learning process to make it easier to learn. which is useful for a. Help make it easier for tutors in learning activities teaching by utilizing media technology in the form of Android-based educational games. Help students learn Chinese HSK material with a happy feeling and don't feel bored, because the content in the educational game "Mandarin Quiz" is displayed in an attractive way with audio, animation, and games on an Android smartphone. Helping children's enthusiasm for learning to know Mandarin. System development for users will be developed using the Multimedia Development Life Cycle (MDLC) methodology. Each step or stage of this method is suitable for system development in multimedia applications and these stages can swap positions according to research needs. It is hoped that the results of testing and designing the Mandarin Quiz educational game application using Unity 2D can be further developed so that this application can help increase interest in learning. The test results and feasibility of this educational game used the Usability Scale System (SUS) which consisted of 46 functions with 10 questions, the final test result was obtained with a score of 88, so that the mandarin quiz educational game was declared acceptable.